A constituição da identidade do professor caboverdiano nas relações sociais e de trabalho - Fortes, Victor Manuel dos Reis Borges (2008)
The objective of this thesis is to understand the identity constitution process of the high school teacher, in Cape Verde, in the social and work relations, and to build, with a prospective scientific material, a legacy to the Cape Verdean literature, for future investigations about the matter. Articulating the social-historical approach elaborated by Vigotski and some more of his followers and the identity theory elaborated by Ciampa, as well as the recourse to several other authors linked to the study of the professors identity and professional character, it is made an analysis of the narratives built in semi-structured interviews with eight teachers chosen from Liceu Amílcar Cabral, in Santa Catarina, Cape Verde. The categories of identity, activity, conscientiousness, meaning and sense and the concept of teaching professional character appear as guidelines for the constitution of an unique and concrete subject that, at the same time, materializes the universal. The theoretical-empirical analysis based on said reference explains that the identity is an unfinished process of continuity, breach and overcoming of the constitution of a subject in his biographic and social relationships, mediated by the meanings and senses he assigned to himself, to his being and action and his place in the world. The interviewed teachers show to be prepared, actuating, critic and with collectivism and humanism sense. They build an identity responsible for their overcoming and promotion, which articulates several phases and circumstances of the life: family, education, emigration, formation, professional exercise of the teaching and social life. It is considered that the objectives proposed in this study were fully achieved, being however opened to different possibilities of interpretation and conclusions, since the identity is a constant process and movement, without absolute results. The theoretical and social relevance of this work may be in the way as the different approaches, categories and concepts were articulated, and in the filling-up of a significant void in the Cape Verdean literature